Advances in engineering materials, structures and systems : innovations, mechanics and applications : proceedings of the 7th International Conference on Structural Engineering, Mechanics, and Computation (SEMC 2019), September 2-4, 2019, Cape Town, South Africa /: innovations, mechanics and applications : proceedings of the 7th International Conference on Structural Engineering, Mechanics, and Computation (SEMC 2019), September 2-4, 2019, Cape Town, South Africa. (2019) - Unknown
No abstract available